Komunikasi Persuasif Kepala Ruang Berpengaruh Terhadap Motivasi Kerja Serta Pendokumentasian Asuhan Keperawatan Di RS X Jakarta Selatan: Indonesia - Trimastuti, Dijaningrum; Tutiany, Tutiany; Soepardi, Sudibyo; Yesayas, Fendy (Jurnal Kesehatan Holistic, 2022)
Nursing services which are one of the duties and responsibilities of nurses are to document the interventions that have been carried out. The purpose of this study was to analyze the impact of persuasive communication training at the head of the room on work motivation and documentation of nursing care at X Hospital, South Jakarta. Quasi Experimental research design using Pre-Post Test Class Design. Respondents in the hegemonic group were 76 respondents who were selected using purposive sampling technique. Respondents in the control group were 25 people. Respondents in the hegemonic group were given persuasive communication coaching as well as supervision and observation for 8 weeks. Collecting data using field information and observation sheets, evaluation of nursing care documentation, then analyzed bivariately with Wilcoxon test and multivariate using Chi-square test and logistic regression. as a result of the study, the average motivation of nurses for the hegemonic group was 28.6%. While the mean of documentation of nursing care in the hegemonic group is 80.2%. there is an impact of persuasive communication training on increasing nurses' motivation (P value < 0.05). there is an impact of persuasive communication training on improving nursing care documentation (Pvalue <0.05). Researchers recommend persuasive communication training in increasing work motivation and documentation of nursing care.